Sonication-assisted emulsification microextraction combined with vortex-assisted porous membrane-protected micro-solid-phase extraction using mixed zeolitic imidazolate frameworks 8 as sorbent - Ge, D. (2014)
10.1016/j.chroma.2012.09.016